Multi-Modulation Sequence Detection using Verilog (International Journal of Food and Nutritional Sciences, 2022)
Modulation classification plays a crucial role in modern wireless communication systems, enabling efficient signal demodulation, spectrum monitoring, and spectrum utilization. A novel multi-modulation sequence detection system has been proposed in this work that integrates MATLAB and Verilog for real-time detection of signals. The proposed system supports BPSK, QPSK, and 16-QAM digital modulations using a fixed-point Q 8.8 format to enhance compatibility with FPGA implementations. Compared to traditional threshold-based and machine learning based methods, the proposed approach achieves higher detection accuracy with lower computational complexity. Extensive simulations demonstrate a detection accuracy of 95%, outperforming conventional classifiers while maintaining real-time processing capabilities. A comparative analysis with existing works highlights the advantages in accuracy, computational efficiency, and robustness against noise. This research lays the foundation for future FPGA-based modulation sequence detection implementations.